Effect of Allium sativum on Immune Status Against Newcastle Disease Virus and Productive Performance of Broiler Chicken - Gautam , Gokarna; Shrestha, Nabaraj; Bhandari, Shishir (International Journal of Poultry Science, 2017)
Objective: This study was conducted to investigate the effect of various levels of garlic (Allium sativum) supplementation in drinking water on immune status against Newcastle disease (ND) virus and productive performance of broiler chicken. Materials and Methods: One hundred and fifty three broiler chickens were brooded together until first week of age. After all chickens vaccinated against ND on day 7, they were randomly allocated to five groups. Control group (n = 30) received no garlic supplementation. Birds in groups T1 (n = 30), T2, T3 and T4 (n = 31 in each group) received 0.2, 0.4, 0.6 and 0.8% (w/v) freshly prepared garlic paste in drinking water respectively, continuously from day 7 through day 42. Second vaccine against ND was given on day 28 to all birds in drinking water. Daily feed intake, weekly weight gain and mortality were recorded. The serum antibody titres against ND virus were determined using hemagglutination-inhibition (HI) test at four periods, 1 and 2 weeks after first and second vaccination against ND. Results: Average live weight gain at day 42 did not differ among five groups. Feed conversion ratio (FCR) was also similar among five groups. Overall mortality rate was the highest in control group (46.7%) and the lowest in T2 group (22.6%). Antibody titres against ND virus antigen were significantly higher in T2 and T3 groups as compared with control group at all four sampling points. Conclusion: Garlic supplementation in drinking water did not affect live weight gain; however, 0.4-0.6% garlic supplementation reduced the mortality and increased the antibody titre against ND virus in broiler chickens vaccinated against Newcastle disease.